2011
DOI: 10.1186/1471-2458-11-s2-s10
|View full text |Cite
|
Sign up to set email alerts
|

The AFHSC-Division of GEIS Operations Predictive Surveillance Program: a multidisciplinary approach for the early detection and response to disease outbreaks

Abstract: The Armed Forces Health Surveillance Center, Division of Global Emerging Infections Surveillance and Response System Operations (AFHSC-GEIS) initiated a coordinated, multidisciplinary program to link data sets and information derived from eco-climatic remote sensing activities, ecologic niche modeling, arthropod vector, animal disease-host/reservoir, and human disease surveillance for febrile illnesses, into a predictive surveillance program that generates advisories and alerts on emerging infectious disease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
(37 reference statements)
0
30
0
Order By: Relevance
“…We found that experts from federal ministries, reference laboratories, and uniformed services had insights on emerging pathogens. Partnerships across national agencies in Africa, such as militaries, have aided in developing surveillance programs for emerging zoonotic diseases (Witt et al 2011;Kronmann et al 2013). Modelers could approach these experts to refine their models.…”
Section: Discussionmentioning
confidence: 99%
“…We found that experts from federal ministries, reference laboratories, and uniformed services had insights on emerging pathogens. Partnerships across national agencies in Africa, such as militaries, have aided in developing surveillance programs for emerging zoonotic diseases (Witt et al 2011;Kronmann et al 2013). Modelers could approach these experts to refine their models.…”
Section: Discussionmentioning
confidence: 99%
“…An example of such a large research network is the EDENext project on the biology and control of vector-borne infections in Europe (87). In another, more narrowly focused research effort, the United States Armed Forces Health Surveillance Center, Division of Global Emerging Infections Surveillance and Response System Operations (AFHSC-GEIS), has developed the RVF prediction project (52) into a worldwide 'predictive surveillance' programme, aimed at the prediction and detection of emerging disease outbreaks, with a particular focus on VBDs such as RVF, JE, leishmaniosis and chikungunya fever (88). Since next-generation sequencing (NGS) technologies became available for metagenomic studies, their use in concert with traditional surveillance methods has allowed for the more rapid discovery and characterisation of new and potentially emerging pathogens from hosts, vectors and reservoirs (89).…”
Section: Surveillance and Researchmentioning
confidence: 99%
“…Several experiments and applied research projects, for example, in the fi eld of surveillance programs, have implemented such integrative approaches, merging together ecological and epidemiological data in multidisciplinary information systems (Witt et al 2011 ). How do these various actors understand the patterns of zoonotic disease emergence and the interactions between environment and health?…”
Section: Business For Biodiversity and Ecosystem Services Valérie Boimentioning
confidence: 99%